Transcatheter mitral valve-in-valve implantation: reports of the first 50 cases from a Latin American Centre. (12th November 2019) - da Costa, Leonardo Paim Nicolau; Palma, José Honório; Barbosa Ribeiro, Henrique; Sampaio, Roney Orismar; Viotto, Guilherme; Medeiros Santos, Romullo; Freitas Tenório, Davi; Saito, Victor Tadami; Egypto Rosa, Vitor Emer; Pinho Moreira, Luiz Felipe; Tarasoutchi, Flavio; Pomerantzeff, Pablo Maria; et al.
Abstract: OBJECTIVES: Our goal was to analyse the initial results of the first 50 transapical transcatheter mitral valve-in-valve procedures performed in a single Latin American centre. METHODS: A prospective, single centre, database analysis was conducted to evaluate immediate, 30-day and 1-year postoperative results of 50 consecutive patients who had a transcatheter mitral valve-in-valve procedure from May 2015 to June 2018. All patients were operated on in a hybrid operating room and received a balloon-expandable valve via the transapical approach. Preoperative and postoperative characteristics were analysed and compared between the first 25 and the second 25 patients to evaluate the impact of the learning curve. Twenty patients had a follow-up examination at 1 year. RESULTS: There was a 98% device success rate. The patients had a mean age of 64.8 years; 72% were women; 80% were in New York Heart Association functional class ≥III preoperatively; and 36% of the procedures were urgent. The mean Society of Thoracic Surgeons scores and EuroSCORE II were 8.3% and 12.4%, respectively. Patients had a median of 2 previous operations; valve durability was 12.1 years; and 64% mitral valve disease of rheumatic fever aetiology. Echocardiography showed decreases in the maximum and mean mitral gradients from 23.5 to 14.6 and 11.5 to 6.4 mmHg postoperatively; the overall mean hospitalization period was 15 days. The overall mortality rate at 30 days was 14%, with 1 intraprocedural death. Further subanalyses between the first and the second half of the cases showed a drop in the mortality rate from 20% to 8% ( P  < 0.01). CONCLUSION: The transcatheter mitral valve-in-valve procedure was shown to be a safe and effective procedure to treat bioprosthetic dysfunction, with potential benefits in patients with rheumatic disease.